The Prognostic Value of Pre-treatment Hemoglobin (Hb) in Patients With Advanced or Metastatic Gastric Cancer Treated With Immunotherapy - Gou, Miaomiao; Zhang, Yong; Liu, Tiee; Qu, Tongtong; Si, Haiyan; Wang, Zhikuan; Yan, Huan; Qian, Niansong; Dai, Guanghai (Frontiers in Oncology, 2021)
Background Biomarkers such as prevailing PD-L1 expression and TMB have been proposed as a way of predicting the outcome of immunotherapy in patients with advanced gastric cancer (AGC) and metastatic gastric cancer (MGC). Our study aims to investigate whether there is a link between pretreatment hemoglobin (Hb) levels and survival to immunotherapy in patients with AGC and MGC. Methods We retrospectively reviewed patients with AGC or MGC treated at the oncology department of the Chinese PLA general hospital receiving PD-1 inhibitor. The Propensity Score Matching (PSM) (1:1) was performed to balance potential baseline confounding factors. Progression-free survival (PFS) and overall survival (OS) was analyzed among different Hb level (normal Hb group and decreased Hb group). Objective response rate (ORR), disease control rate (DCR) were also analyzed. Univariate analysis and multivariate analysis were performed further to validate the prognostic value of Hb level. Results We included 137 patients with AGC and MGC who received PD-1 inhibitors (including Pembrolizumab, Nivolumab, Sintilimab, Toripalimab) in this study. After PSM matching, there were no significant differences between the two groups for baseline characteristics. Within the matched cohort, the median PFS was 7.8 months in the normal Hb level group and 4.3 months in the decreased Hb group (HR 95% CI 0.5(0.31, 0.81), P=0.004). The OS was 14.4 months with normal Hb level as compared with 8.2 months with decreased Hb level(HR 95% CI 0.59(0.37, 0.94), P=0.024). The ORR was 40.7% and DCR was 83.0% in the normal Hb group, while the ORR was 25.5% and DCR was 85.1% in the decreased Hb group. No significant differences were found in the ORR and DCR between the two groups (P=0.127, P=0.779). Univariate analysis and multivariate analysis showed that Hb level was only independent predictor for PFS and baseline Hb level was significant prognostic factor influencing the OS. Only when patients had normal Hb level, anti-pd-1 monotherapy or combined with chemotherapy was superior to anti-pd-1 plus anti-angiogenic therapy with respect to PFS (10.3 m vs 2.8 m, HR 95% CI 0.37(0.15, 0.95), P=0.031) and OS(15 m vs 5.7 m, HR 95% CI 0.21 (0.08, 0.58), P=0.001). Conclusions Our study have demonstrated that pretreatment Hb level was an independent prognostic biomarker in term of PFS and OS with immunotherapy for AGC and MGC patients. Correction of anemia for GC patients as immunotherapy would be a strategy to improve the survival. More data was warranted to further influence this finding.